Perancangan Ulang Desain UI/UX Website Digilib Universitas Sriwijaya Menggunakan Metode Double Diamond - Rahman, Fachri Auliya; Indah, Dwi Rosa (JURNAL FASILKOM, 2024)
System digitalization is an effort to improve quality to make it easier for users to manage the system digitally. Library digitalization aims to connect the interaction of the general public and information sources from the library without any interaction. Sriwijaya University State University facilitates student learning sequences in terms of submitting documents and searching for research and journals with Sriwijaya University's digital library called Digilib Unsri. However, based on an initial survey that was conducted with 30 respondents using the webuse method which was divided into 4 dimensions, namely (Content, Organization & Readability, Navigation & Links, User Interface Design, and Performance & Effectiveness), stated that the satisfaction points for using the website were only of 0.55 with the level of use being at a moderate level. This is caused by several reasons, such as unclear website usage guidelines, feature functions that are difficult to understand, unattractive design appearance, and a display that is less user friendly. To overcome this, the author redesigned the interface design on the Digilib Unsri website using the Double Diamond method which is divided into 4 stages, namely discover, define, develop, and delivery. website with points of 0.85 and is at the "excellent" usage level. From these results, it can be seen whether the new design of the Digilib website prototype is accepted by users. This research uses webuse to measure website interface design, it is recommended that further research use other usability testing methods as a measuring tool for interface planning.